The Eucharistic Sending: Reconstructing The Sending Narratives in Sunday Worship - Ricky Pramono Hasibuan (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
This article explores the importance of the Sending in the Sunday Worship, which is crucial to support people's daily lives as it bridges the gap between every Sunday service where people worship. The narrative of the Sending must be appropriately formulated to ensure that people can implement it effectively. Currently, the narrative is often based on weekly changing sermon content, leading to unfinished tasks accumulating without evaluation. To address this issue, this article proposes that the Sending narrative should be based on the remembrance of The Lord's Supper, which is the main element of Sunday worship besides the sermon. By using Jesus' words “do this!” as a potential basis for sending people into everyday life, this article argues that individuals can be encouraged to fulfill their role in showing love to others.